LED lighting. Creation and application peculiarities - Trofimov, Yu.V.; Lishik, S.I.; Posedko, V.S.; Tsvirko, V.I.; Pautino, А.А. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
State-of-the-art condition of LED illumination engineering for street lighting, its requirements, construction technological features of its creation, optimization ways of optical, thermal and electrical luminaire subsystems are considered in this article. Besides, the results of own researches and development in the field of outside lighting are reported here.